Reaching Farmers through Cyber Corridor - R.K Sohane,; Aditya,; U.S Jaiswal, (Journal of Agricultural Extension Management, 2015)
India is on the track to embark upon a "Cyber revolution" with effective reach and access through the use of Information and Communication Technologies (ICTs). With the effective progress made in agriculture, information technology and Cyber extension has the potential to play a vital role in transforming India into a "cyber-enabled agriculture" in the 21'1 century. The present paper deals with the important ICT tools used in Bihar Agricultural University for reaching the farmers, to enable better farming in the state